L’espace domestique des migrants marocains : les extensions transnationales de l’intimité familiale - Jordan Pinel; Thomas Lacroix (Ambiances)
The aging of North African migrants has spurred a renewal of scholarly interest in their residential practices. Many of them have chosen to share their existence between their housing in France and the one they acquired in Morocco. Retirement appears more like the age of back-and-forth movements rather than the one of return. Studying the interior design of their home, this paper questions the idea that migrants overinvest in their homeland housing in order to appear as a member of the local elite and hide the stigma of their working-class condition. What stands out of the field study is rather the will to build a residential continuum through the mise en resonance (i.e. the building of a space through interconnected objects) of interior designs. Migrants display the will to build a space for family intimacy beyond legal and cultural discontinuities.